Magnetic Resonance Texture Analysis in Myocardial Infarction - Peng, Fei; Zheng, Tian; Tang, Xiaoping; Liu, Qiao; Sun, Zijing; Feng, Zhaofeng; Zhao, Heng; Gong, Lianggeng (Frontiers in Cardiovascular Medicine, 2021)
Texture analysis is a newly arisen field that can detect the invisible Magnetic resonance imaging signal changes among image pixels. Myocardial infarction is cardiomyocyte necrosis caused by myocardial ischemia and hypoxia, becoming the primary cause of death and disability worldwide. In recent years, various texture analysis studies have been performed in patients with myocardial infarction and show a good clinical application prospect. This review briefly presents the main pathogenesis and pathophysiology of myocardial infarction, introduces the overview and workflow of texture analysis, and summarizes multiple magnetic resonance texture analysis clinical applications in myocardial infarction. We also discuss the facing challenges currently for clinical utilization and propose the prospect.